Acting for Auntie: from studio realism to location realism in BBC television drama, 1953-2008 - Hewett, Richard (2012)
Acting for television has hitherto been a much-neglected field; by focusing solely on screen performance, usually via textual analysis, the small amount of work thus far conducted has largely ignored the various conditioning factors that combine to shape it. This thesis is designed to address that lack, drawing on a combination of archive research, original interviews and textual analysis to provide a multi-perspectival, historical overview of acting in British television drama, spanning the live era to the present day. The programmes selected as case studies herein derive from historically distinct production contexts: namely, the live drama of The Quatermass Experiment (BBC, 1953); the ‘as live’, pre-recorded videotape of Doctor Who (BBC, 1963-89); and the move to Outside Broadcast location work, utilising a ‘rehearse/record’ process, on the first series of Survivors (BBC, 1975-77). The fact that each programme has since been re-made in the 2000s allows for both a comparative study and a chronological development of television acting. The significance for acting of the shift from multi-camera studio to single camera location work is represented here by the models of studio realism and location realism. However, the physical site of performance is just one of several determinants that are examined throughout. Actor experience, technology, drama training and production process together comprise a complex set of variables that are in a constant state of flux. How these factors have intersected and combined to affect performance provides the key to this study of British television acting over the last six decades.